New View on the Analysis of Enterprises Activities - Brazaitis, Zenonas; Subačienė, Rasa (Ekonomika, 2006)
Nowadays, under intensive and dynamic conditions of economy it is not easy not only to create a business but also to retain it and develop. Lithuania’s integration into the common market of the European Union, its active participation in the international markets as well as competitiveness growth on the domestic market amongst local rivals entails actually to markedly strengthen analysis and realistically assess own financial state and that of the rivals as well as to foresee further development of the business and its perspectives. Accordingly. to sort out the problems mentioned above it is necessary to accomplish an analysis of businesses (enterprises). Prof. J. Mackevičius monograph “Analysis of the business” contains issues like analysis of the business (its activity), collection of information, its processing and assessment. Analysis of the business activity is accomplished through research of dynamics and structure of different indicators, their interrelationship and dependence as well as factors that prompt the changes of indicators are discovered. Thus, the said monograph is particularly helpful for business (enterprise) managers, accountants, auditors and other specialists within the remit of analysis of the business problems.